NILAI TAMBAH DAN KEUNTUNGAN PENGOLAHAN BUNGA KRISAN PADA BERKAT ANUGERAH FLORIST DI KELURAHAN KAKASKASEN I, TOMOHON UTARA (Added Value And Profit Of Chrysanthemum Flower Processing At Berkat Anugerah Florist In Kakaskasen I Village, Tomohon Utara) - Hilya S. R. Qishma; Jelly R. D. Lumingkewas; Agnes E. Loho (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
Chrysanthemum flower is a type of ornamental flower plant cultivated in Indonesia which has good prospects for development and becomes a source of income that generates added value due to the inclusion of primary product processing elements into new products. The objective of this research is to analyze the benefits and added value of chrysanthemum flowers at the Berkat Anugerah Florist in Kakaskasen I Village, North Tomohon Sub District, Tomohon City. The benefit of this research is that it can provide a source of information about the added value and benefits of chrysanthemum. Methods of data collection, namely primary and secondary data as well as the variables measured in this study for a series of hanging round cranes, standard standing cranes, large standing cranes and table flowers. The results of the data obtained will then be processed and analyzed in more depth using added value analysis according to the hayami method. The research result showed that has been done showed that flower arrangements at the Florist which provide added value as follows for large standing bouquets have the greatest added value with an added value of Rp. 32,907.08, two hanging round cranes with an added value of Rp. 14,017.21, the three table flowers with an added value of Rp. 7,602.22 and finally a standard standing crane with an added value of Rp. 7,377.78. Meanwhile, the biggest profit for business owners is a large standing crane with a profit of Rp. 32407.08. Then the hanging crane with a profit of Rp. 13017.21. Standard standing faucet with a profit of Rp. 6,477.77. Table interest with the smallest profit of Rp. 6.102,22.